Research on the influence path of red tourism experience on tourists’ well-being: based on the chain mediating role of tourists’ emotion and national identity - Huiling Zhou; Qianru Zhang; Lu Lu; Yajun Jiang; Ke Wu (BMC Psychology)
Abstract Background Red tourism is a way of tourism with Chinese characteristics, carrying tourists’ fresh emotions and value pursuit, and is an important part of the construction of tourists’ well-being. Methods Based on the stimulus-organic-response (SOR) theory and taking tourists’ emotion and national identity as the mediating factors, this study researched on the mechanism of tourists’ well-being in red tourism by constructing a structural equation model of red tourism experience and tourists’ well-being. Results (a) Red tourism experience has a significant positive impact on tourists’ emotions (positive emotion and positive negative emotion), and tourists’ emotions also have a significant positive impact on national identity; (b) Positive emotion and national identity have significant positive effects on tourists’ well-being; (c) Tourists’ emotions and national identity play a mediating role between red tourism experience and tourists’ well-being. Conclusion This study provides a valuable supplement to the literature on tourists’ well-being in the context of red tourism, and the research results provide a new perspective and theoretical basis for the managers of red tourism destinations to formulate marketing strategies.